Intestinal Alkaline Phosphatase as a Thrombogenic and Platelet-Altering Factor in Rabbits - Iatridis, S. G; Ferguson, J. H; Iatridis, P. G (Thrombosis and Haemostasis, 1970)
Purified intestinal alkaline phosphatase (AlPh), 10 mg/kg, was injected intravenously into rabbits. In normal animals, 1 min post-injection, averaged samples showed platelet count decreases to 50% of control values in whole blood and to 20% in centrifuged “platelet-rich” plasma. Small or large platelet aggregates were noted in the counting chambers, and a glass-bead platelet-adhesiveness test gave values at least twice that in the controls. The platelet changes were paralleled by shortening of an ear-lobe bleeding-time test and by an equally temporary shortening of the r and h values in thrombelastograms (TEG) of fresh whole blood. A very significant correlation, in the 1 min data, was with 4 + thrombosis in 30 min occluded test segments of mesenteric veins. Screening tests of coagulation and fibrinolysis were not significantly altered, and the same was true of various clotting factor assays, except perhaps for small changes which might be attributable to limited local clot formation.15 min post-injection, platelet counts had risen again, no aggregates were noted, the TEG normalized, and the thrombosis test was negative.In dicumarolized rabbits, the AlPh injections still elevated the serum alkaline phosphatase and caused the platelet alterations, but now without the thrombophilic changes.Electrophoretic studies of AlPh isoenzyme distribution suggested that the significant post-injection elevations were not those in the total serum or beta-globvlin enzyme levels, but in a specific “gamma” isoenzyme, migrating cathodic to the ß-globulins.The significance of the present experiments to the basic understanding and testings of thrombotic states is briefly discussed.